Chinese college students COVID-19 phobia and negative moods: Moderating effects of physical exercise behavior - Han, Shan-shan; Han, Ya-hui; Tong, Wen-xia; Wang, Guang-xu; Ke, You-zhi; Meng, Shu-qiao; Guo, Qiang; Cui, Zhong-lei; Zhang, Jun-yong; Ye, Yu-peng; Zhang, Yao; Li, Ya-xing; et al. (Frontiers in Public Health, 2022)
Objective: We investigated the effects of COVID-19 fear on negative moods among college students, and assessed the efficacy of physical exercise behavior as a moderator variable. Methods: This was a cross-sectional study. Students from three colleges and universities in Shangqiu City, Henan Province and Yangzhou City, Jiangsu Province were enrolled in this study, which was performed during the COVID-19 pandemic using an online questionnaire. A total of 3133 college students completed the questionnaire. Measurement tools included the COVID-19 Phobia Scale (C19P-S), Depression-Anxiety-Stress Self-Rating Scale (DASS), and the Physical Activity Behavior Scale (PARS-3). Results: During the COVID-19 pandemic, the rates of depression, anxiety, and stressful negative moods among college students were 35.5%, 65.5%, and 10.95%, respectively; there was a positive correlation between COVID-19 fear and negative moods among college students (r=0.479, p <0.001), which was negatively correlated with physical exercise behavior (r=-0.4, p<0.001); the regulating effects of physical exercise behavior were significant (△R2=0.04, p<0.001). Conclusion: The rate of negative moods among college students is high, and the fear for COVID-19 is one of the key factors that lead to negative moods. Physical exercise can modulate the impact of COVID-19 fear among college students on negative moods. Studies should elucidate on mental health issues among different populations during the COVID-19 pandemic.